PENGARUH MANAJERIAL KEPALA SEKOLAH DAN KOMPETENSI GURU TERHADAP KINERJA GURU - Dwi Fitri Apriani; Paiman Raharjo (PUBLIKA: Jurnal Ilmiah Administrasi dan Kebijakan Publik, 2021)
Dr.The aim of this study is to test the relation between School Head Master Managerial and Teacher Competency with Teacher Performance. The research population is all school within North Bogor area. There are 107 selected respondents and interviewed using prepared instrument. The validity and reliability test show that the instrument pass the test, hence able to be used in this study. The result of the study shows there is a good relationship between School Head Master Managerial and Teacher Competency with Teacher Performance. The determnination effect is 86,3%. The individual relation between School Head Master Managerial with Teacher Performance is 90,8% and between Teacher Competency with Teacher Performance is 70,1%..